Shifaraw bafidalat se el - Wondeye Ali. (Rehobot Astamiwoch; Addis Ababa., 2013)
A biography of Shefaraw Woldemika'ľ an Ethiopian lawyer and first Minister of Justice.
Includes bibliographical references.
In Amharic.
Keywords: 1944-; Lawyers -- Ethiopia -- Biography; Justice ministers -- Ethiopia -- Biography